Impact Of Inflow Of Fid On Select Macro Economic Variables (The Review of Diabetic Studies, 2025)
This study examinesand explores the relationship among foreign direct investment (FDI) inflows on key economic variables in India between 2021 and 2023. Despite extensive literature on FDI in India, a gap exists in analysing its effects using descriptive statistics on GDP, exports, exchange rates, aggregate income of the country and price Index. The research employs secondary data from Reserve Bank of India publications and statistical tools such as SPSS. Findings reveal varied stability in FDI inflows, with countries like Singapore showing low variability, while others like Canada exhibit high fluctuations. Significant changes in economic indicators include an increase in exports, inflationary pressures, rupee depreciation, and GDP growth. These results suggest the need for tailored policies to stabilize FDI inflows,manage inflation, and enhance trade. Overall, the study highlights mixed economic stabilityand performance, underscoring both growth opportunities and challenges for India.